The Uvalde school shooter: uncovering the dreadful story behind an antisocial profile - Ramos-Galarza, Carlos; Obregón, Jennifer (Frontiers in Behavioral Neuroscience, 2025)
IntroductionThe case of the Texas shooter is an event that marked human history, as an 18-year-old young man cold-bloodedly murdered 21 victims.ObjectiveTo analyze the psychological factors that could explain the antisocial behavior of the case under study.MethodologyThrough clinical behavioral analysis and data collection from the case, a psychological profile was constructed to identify specific factors that provide greater clarity regarding the risk factors associated with the violent act, which enabled the development of this perspective article.ResultsThe study delves into several factors that could be considered determining and causal to the antisocial behavior in this case, including child abuse, family violence, bullying, animal cruelty, the impact of maltreatment on brain development, and the relationship between antisocial behavior and the use of violent video games.DiscussionThe analysis concludes by emphasizing the need to identify the causal factors of antisocial behavior in the early stages of human development. Additionally, it highlights the importance of implementing early interventions that can positively influence the factors described in this article.